Enhancing Creative Thinking Skills through Project-Based Learning Assisted Game Open Online Physics Instructional - Firmanul Catur Wibowo; Nur Jahan Ahmad (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
This study aims to enhance creative thinking skills through Project-Based Learning (PjBL) assisted Game Open Online Physics Instructional (GOOPI). GOOPI is an online game-based physics learning media and contains physics concepts found on the page: https://goopi.id/ (use UC browser). The research method used is a quasi-experimental design with two experimental groups and one control group. The sample of this study was 75 eighth grade students from a province in Indonesia. GOOPI technology as software developed to support PjBL activities in the classroom. The results of the research show that project-based learning assisted GOOPI can enhance creative thinking skills. Based on statistical calculations there is an increase in the gain value, an increase of 0.72 in the high category for the PjBl experimental group 1 with GOOPI, the PjBl experimental group 2 alone experienced an increase in the gain value of 0.55 in the medium category, and the group with the teacher based instructional method experienced an increase in the gain value of 0, 45 medium categories. It is suggested that GOOPI technology can be an interesting and effective tool to activate students' positive interest in the PJBL process. In addition, the implications of applying GOOPI for physics learning and recommendations for further study are discussed in this study.